2020
DOI: 10.1155/2020/8863900
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Unprovoked Venous Thrombosis (Cerebral Sinus Thrombosis and Mesenteric Vein Thrombosis) in Young Patient with Crohn’s Disease: A Case Report and Review

Abstract: Inflammatory bowel disease (IBD) patients have a higher risk of thrombosis. Most data about thrombosis in inflammatory bowel disease are related mainly to inpatients with disease activity, but in this article, we report one case of inflammatory bowel disease with two different sites of venous thrombosis which happened in a patient with nonactive IBD at an outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Pathologically, the patient had changes in the crypts (Figures 2A,B), similar to those seen in CD. Moreover, CD has been reported with extensive thrombosis in the limbs and CVST (15)(16)(17)(18)(19). A study has reported that the thrombosis prevalence among patients with CD is 5.7% (20).…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, the patient had changes in the crypts (Figures 2A,B), similar to those seen in CD. Moreover, CD has been reported with extensive thrombosis in the limbs and CVST (15)(16)(17)(18)(19). A study has reported that the thrombosis prevalence among patients with CD is 5.7% (20).…”
Section: Discussionmentioning
confidence: 99%